Proteomics in Schizophrenia: A Gateway to Discover Potential Biomarkers of Psychoneuroimmune Pathways - Rodrigues-Amorim, Daniela; Rivera-Baltanás, Tania; Vallejo-Curto, María del Carmen; Rodriguez-Jamardo, Cynthia; de las Heras, Elena; Barreiro-Villar, Carolina; Blanco-Formoso, María; Fernández-Palleiro, Patricia; Álvarez-Ariza, María; López, Marta; García-Caballero, Alejandro; Olivares, José Manuel; et al. (Frontiers in Psychiatry, 2019)
Schizophrenia is a chronic, severe and disabling psychiatric disorder with a complex neurobiological pathophysiology that translates into an ambiguous aetiology. The lack of consensus regarding the pathogenesis of this ailment has increased the need to explore new research lines in this regard. Advances in “omics” sciences, such as proteomics, promotes new approaches to better understand the molecular basis of schizophrenia and identify potential biomarkers. This research makes use of proteomics data to discover possible analytes associated with psychoneuroimmune signalling pathways in schizophrenia. Methods: A comparative proteomic analysis was performed on the plasma of 45 patients with schizophrenia and 43 healthy subjects, and label-free liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to identify and quantify proteomes. Protein immunoblot analyses were carried out to evidence the proteomics results. Results: Upon quantification, the analysis revealed a significant reduction in the levels of glia maturation factor beta (GMF-β) (P=0.0256), the brain-derived neurotrophic factor (BDNF) (P=0.0008), and the 115-kDa isoform of the Rab3 GTPase-activating protein catalytic subunit (RAB3GAP1) (P=0.0002) in patients with schizophrenia as compared to healthy volunteers. Statistical significance was also founded between the groups of first-episode schizophrenia (FES) and chronic schizophrenia compared to controls concerning the levels of BDNF (P=0.0031; P=0.0131), 115-kDa isoform of RAB3GAP1 (P=0.0080; P=0.0020), respectively, and GMF-β levels in the chronic schizophrenia group (P=0.0453). Attractin, drebrin and RAB3GAP1 did not yield significant results, as well as, correlations of proteins levels with PANSS scores (P >0.05). Conclusion: The GMF-β, BDNF, and 115-kDa isoform of RAB3GAP1 are associated with different biological mechanisms taking place in the central nervous system, thus making them potential biomarkers in schizophrenia